Efficacy of Acupuncture in the Treatment of Essential Hypertension: An Overview of Systematic Reviews and Meta-Analyses - Maoxia Fan; Guohua Dai; Runmin Li; Xiaoqi Wu (Cardiovascular Therapeutics)
Background. Acupuncture is widely used in the clinical treatment of essential hypertension (EH). This overview is aimed at summarizing current systematic reviews of acupuncture for EH and assessing the methodological bias and quality of evidence. Methods. Two researchers searched and extracted 7 databases for systematic reviews (SRs)/meta-analyses (MAs) and independently assessed the methodological quality, risk of bias, reporting quality, and quality of evidence of randomized controlled trials (RCTs) included in the SRs/MAs. Tools used included the measurement tool to assess systematic reviews 2 (AMSTAR-2), the risk of bias in systematic (ROBIS) scale, the checklist of preferred reporting items for systematic reviews and meta-analyses (PRISMA), and the grading of recommendations assessment, development, and evaluation (GRADE) system. Results. This overview included 14 SRs/MAs that use quantitative calculations to comprehensively assess the various effects of acupuncture in essential hypertension interventions. The methodological quality, reporting quality, risk of bias, and quality of evidence for outcome measures of SRs/MAs were all unsatisfactory. According to the results of the AMSTAR-2 assessment, all SRs/MAs were of low or very low quality. According to the results of the ROBIS evaluation, a few SRs/MAs were assessed as low risk of bias. According to the results of the PRISMA checklist assessment, SRs/MAs that were not fully reported on the checklist accounted for the majority. According to the GRADE system, 86 outcomes were assessed under different interventions in SRs/MAs, and 2 were rated as moderate-quality evidence, 23 as low-quality evidence, and 61 as very low-quality evidence. Limitations of the included SRs/MAs included the lack of necessary items, such as not being registered in the protocol, not providing a list of excluded studies, and not analyzing and addressing the risk of bias. Conclusion. Currently, acupuncture may be an effective and safe treatment for EH, but the quality of evidence is low, and caution should be exercised when applying this evidence in clinical practice.